Rare C-6 vertebral involvement in a child with histiocytosis X: Case report - Salehpour, Firouz; Tubbs, Shane R.; Zarrintan, Sina; Meshkini, Ali; Hadidchi, Shahram; Pourfathi, Hojjat; Azhough, Ramin; Fakhrjou, Asharf; Goodrich, James T.; Khaki, Amir Afshin (Folia Neuropathologica, 2007)
The authors present a rare case of C-6 vertebral involvement in a 12-year-old boy with histiocytosis X. The patient presented with limitation in movements of neck and upper extremities. Computed tomography (CT) and magnetic resonance (MRI) imaging were used in the preoperative workup. Surgery was performed via an anterior cervical approach along with stabilization using a fibula strut graft and plate fixation. Pathological assessment showed infiltration of Langerhans cells accompanied by a mixture of many eosinophils, giant cells, neutrophils and foamy cells. The patient went on to make a full recovery with complete resolution of his motor weakness. In an extensive review of the literature there are very few cases of cervical histiocytosis X reported. In addition, surgical management of this type of lesion has rarely been discussed.